Exploring the Affiliation between Integrated Reporting and Firm Performance: Evidence from Bangladesh - Shahria, Golam (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
The objective of this study is to assess the extent of integrated reporting (IR) practice with reference to the disclosure pattern and to examine its association with financial performance and market growth in the voluntary disclosure of manufacturing companies in Bangladesh. Samples of this study are 41 manufacturing companies from nine different industries listed in Dhaka Stock Exchange (DSE). The total observations were 123 firm year observations. Using two-stage-least-squares approach to reduce endogeneity concerns, this study reveals that Integrated Reporting Index (IRDINX) is positively and significantly related with firm performance. However, the relationship between IRDINX and growth is positive but insignificant. The content analysis found an increasing pattern of IR disclosure by the sample firms. The findings of this study encourage firms to adopt IR practice and add value to the existing literature as very few researches have been done on IR area in Bangladesh.